2015
DOI: 10.1007/s10551-015-2679-0
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committees and Financial Reporting Quality in Singapore

Abstract: We examine three characteristics (independence, expertise, and overlapping membership) of audit committees and their impact on the financial reporting quality for Singapore-listed companies. The main finding is that financial reporting quality will be higher if audit committees have mixed expertise in accounting, finance, and/or supervisory. In addition, we do not find evidence that incremental independence of audit committees enhances financial reporting quality because audit committees already consist of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
109
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 26 publications
18
109
2
3
Order By: Relevance
“…As an accounting and auditing specialist, a board accountant also helps to monitor the ability of the management to make economic choices and offers experience-based views on the control of the financial statements of the firm (Klein 2002). Furthermore, the study of Kusnadi et al (2016) outlined the evidence from Singaporean firms that accounting specialists on the board encourage the quality of financial reporting substantially. They further confirmed these outcomes by considering both accounting and economic specialists and reporting the same outcomes, noting that accounting specialists act as a watchdog on the company's financial reporting system (Kusnadi et al 2016;Masud et al 2019).…”
Section: Accounting Experts On the Boardmentioning
confidence: 99%
See 1 more Smart Citation
“…As an accounting and auditing specialist, a board accountant also helps to monitor the ability of the management to make economic choices and offers experience-based views on the control of the financial statements of the firm (Klein 2002). Furthermore, the study of Kusnadi et al (2016) outlined the evidence from Singaporean firms that accounting specialists on the board encourage the quality of financial reporting substantially. They further confirmed these outcomes by considering both accounting and economic specialists and reporting the same outcomes, noting that accounting specialists act as a watchdog on the company's financial reporting system (Kusnadi et al 2016;Masud et al 2019).…”
Section: Accounting Experts On the Boardmentioning
confidence: 99%
“…Furthermore, the study of Kusnadi et al (2016) outlined the evidence from Singaporean firms that accounting specialists on the board encourage the quality of financial reporting substantially. They further confirmed these outcomes by considering both accounting and economic specialists and reporting the same outcomes, noting that accounting specialists act as a watchdog on the company's financial reporting system (Kusnadi et al 2016;Masud et al 2019). Accounting experts of a firm always concentrate on the profitability of a firm rather than the sustainability of that firm.…”
Section: Accounting Experts On the Boardmentioning
confidence: 99%
“…Moreover, Pucheta-Martínez & de Fuentes [38] discover that AC independence is a negatively significant relationship at the 10% level with the reforms of audit opinion for noncompliance with GAAP. Antagonistically, this study did not discover any correlation between AC independence and quality of financial reporting [54,4,15,9]. However, the relationship between AC independence and modified audit opinion in Jordan remains unclear.…”
Section: Independence Of Audit Committeementioning
confidence: 73%
“…Empirical researches showed conflicting results with respect to the influence of AC size on the quality of financial reporting. Some of these showed that the size of the AC has a substantial negative relationship with the quality of financial reporting [4,9]. This suggests that the big size of AC would have superior control and overseeing role that has the potential to transform into a better quality of financial statements because of more participation and ideas.…”
Section: Size Of Audit Committeementioning
confidence: 99%
See 1 more Smart Citation